Pengaruh Visual Merchandising, Store Atmosphere dan Hedonic Shopping Motivation Terhadap Impuls Buying Pada Toko Maya Collection Beleke Lombok Barat - Farid Wajdi; Muh. Mujahid Dakwah (Postgraduate, University of Mataram, 2025)
This study aims to examine the influence of Visual Merchandising, Store Atmosphere, and Hedonic Shopping Motivation on Impulse Buying at Maya Collection store. This research adopts a quantitative approach using a non-probability sampling method and involves 100 respondents as the sample. The data analysis technique employed is regression analysis to measure the relationship between variables. The results indicate that Visual Merchandising and Store Atmosphere do not have a significant effect on Impulse Buying, with significance values of 0.487 and 0.580, respectively. Meanwhile, Hedonic Shopping Motivation has a significant effect on Impulse Buying, with a significance value of 0.039. These findings suggest that hedonic shopping motivation plays an important role in driving consumers' impulse buying behavior, while store display and atmosphere do not have a significant impact.